Public Relations Management in Improving the Image of Educational Institutions - Izza Nila Syarifah; Azzah Nor Laila (Center for Studies in Advanced Science, 2025)
This thesis is the result of research that presents problems with public relations management in the image of MTsN 1 Kediri. The purpose of this study is to find out how public relations management is carried out in MTsN 1 Kediri. The research method used in this study is descriptive qualitative, which is an effort made to reveal facts, data, and phenomena that occur in the field. This research uses a case study approach and the type of research used is field. The results of this study show, that: 1) Public relations management planning on the image of MTsN 1 Kediri, namely by planning programs that aim to attract public attention to create a positive image in madrasa; 2) Implementation of public relations management on the image of MTsN 1 Kediri, namely by implementing planned programs by promoting madrasah through social media, holding and increasing cooperation with other institutions and the surrounding community, maximizing the implementation of public relations programs with strategies carried out; 3) Evaluation of public relations management on the image of MTsN 1 Kediri is carried out once a semester and after the implementation of the activity program, then improvements are made in the future.